Tobacco manufacturers' defence against plaintiffs' claims of cancer causation: throwing mud at the wall and hoping some of it will stick. (27th November 2006) - Milberger, Sharon; Davis, Ronald M; Douglas, Clifford E; Beasley, John K; Burns, David; Houston, Thomas; Shopland, Donald
Abstract : Background: In the late 1990s and the early part of this decade, the major US cigarette manufacturers admitted, to varying degrees, that smoking causes cancer and other diseases. Objective: To examine how tobacco manufacturers have defended themselves against charges that their products caused cancer in plaintiffs in 34 personal injury lawsuits, all but one of which were litigated between the years 1986 and 2003. Methods: Defence opening and closing statements, trial testimony, and depositions for these cases were obtained from the Tobacco Deposition and Trial Testimony Archive (http://tobaccodocuments.org/datta/ ). All available defence-related transcripts from these cases were reviewed and a content analysis was conducted to identify common themes in the defendants' arguments. Results: After review of the transcripts, defendants' arguments were grouped into seven categories: (1) there is no scientific proof that cigarette smoking causes lung cancer; (2) the plaintiff did not have lung cancer as claimed; (3) the plaintiff had a type of lung cancer not associated with cigarette smoking; (4) the plaintiff had cancer that may have been associated with cigarette smoking or smokeless tobacco use, but tobacco products were not to blame in this particular case; (5) the plaintiff had cancer that may have been associated with cigarette smoking, but the defendant's cigarette brands were not to blame; (6) the defendant's cigarettes (or smokeless tobacco) may have played a role in the plaintiff's illness/death, but other risk factors were present that negate or mitigate the defendant's responsibility; and (7) the defendant's cigarettes may have been a factor in the plaintiff's illness/death, but the plaintiff knew of the health risks and exercised free will in choosing to smoke and declining to quit. Use of the argument that smoking is not a proven cause of lung cancer declined in frequency during and after the period when tobacco companies began to publicly admit that smoking causes disease. Corresponding increases occurred over time in the use of other arguments (namely, presence of other risk factors and "free will"). Conclusions: Despite the vast body of literature showing that cigarette smoking causes cancer, and despite tobacco companies' recent admissions that smoking causes cancer, defendants used numerous arguments in these cases to deny that their products had caused cancer in plaintiffs. The cigarette companies, through their public admissions and courtroom arguments, seem to be saying, "Yes, smoking causes lung cancer, but not in people who sue us".